TINDAKAN PENCEGAHAN MALARIA DI DESA SUDOROGO KECAMATAN KALIGESING KABUPATEN PURWOREJO - Restu Alami; Retno Adriyani (Jurnal Promkes: The Indonesian Journal of Health Promotion and Health Education, 2016)
Malaria is a parasitic disease that is still a public health problem in Indonesia. Public awareness of the dangers of malaria will aff ect the precautions taken. This study aimed to analyze the measures of prevention of malaria in the Sudorogo village Kaligesing District of Purworejo. This study used a case control approach. Sample of this study consisted of 20 cases and 20 controls were taken using simple random sampling technique. The study was conducted from July 2016 to January 2017. The instrument that used in this research was questionnaires and observation sheets. The collected data were analyzed using simple logistic regression. The results of the analysis, indicated that the society actions are habit to stayed outside home in the evening; conducting environmental health habits; habit of not wearing mosquito repellent during the night; habit of not wearing repellent when outdoors activity at night; and the habit of not wearing long sleeves and long pants when out at night did not showany signifi cant correlations with the incidence of malaria in the area of research. Variables that showed a signifi cant correlation with the incidence of malaria in the area of research is the habit of not using mosquito nets while sleeping at night with a p value of 0.012 (95% CI 1.529 to 31.377). The conclusion of this study was there is correlation between habit of not usingmosquito nets while sleeping with the incidence of malaria in the Sudorogo village Kaligesing District of Purworejo.Keywords: preventive action, the incidence of malaria